-4(8v-7)+6(-4v-1)=22

Simple and best practice solution for -4(8v-7)+6(-4v-1)=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(8v-7)+6(-4v-1)=22 equation:


Simplifying
-4(8v + -7) + 6(-4v + -1) = 22

Reorder the terms:
-4(-7 + 8v) + 6(-4v + -1) = 22
(-7 * -4 + 8v * -4) + 6(-4v + -1) = 22
(28 + -32v) + 6(-4v + -1) = 22

Reorder the terms:
28 + -32v + 6(-1 + -4v) = 22
28 + -32v + (-1 * 6 + -4v * 6) = 22
28 + -32v + (-6 + -24v) = 22

Reorder the terms:
28 + -6 + -32v + -24v = 22

Combine like terms: 28 + -6 = 22
22 + -32v + -24v = 22

Combine like terms: -32v + -24v = -56v
22 + -56v = 22

Add '-22' to each side of the equation.
22 + -22 + -56v = 22 + -22

Combine like terms: 22 + -22 = 0
0 + -56v = 22 + -22
-56v = 22 + -22

Combine like terms: 22 + -22 = 0
-56v = 0

Solving
-56v = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Divide each side by '-56'.
v = 0

Simplifying
v = 0

See similar equations:

| -5x+30=-3x+50 | | x+52+x+119=163 | | 4.3+10m=8.49 | | 2x^2=-8x+10x | | 2m+8+m=-3 | | 3(3-d)-19=17d-5(2+4d) | | 13x+5=14x-7 | | 8=x-square(x-6) | | ab+3b= | | 14-2m=26 | | 6x-3=6(x+9) | | 3q-11=61-3q | | 2y-12+3y=6+5y | | 3x+4=-8-5x | | 3x+8-2x=9+4x-7 | | 2+3.5(z+2)=5.5z-5 | | 8(x+2)+6(x+2)=7x-7 | | 6(z^2+1)=-13z | | x(5x+17)=2x^2-5x+16 | | 1+109x+45x-1=154 | | 9m^2+144=78m | | 4(x+8)=x+5 | | 0.55x+0.3x=x-10.5 | | 4(3x-2y)=(3y-2x) | | (3x-9)(x^2-4x-x+4)+(2x-4)(x^2-4x-x+4)=(4x-12)(x^2-4x-2x+8)+(x-3)(x^2-x-2x+2) | | 12-k-2=6k-11 | | 8x^3-4x^2+7x-1=0 | | 0.4x+3.6=0.3x+1.3 | | (3x-4)+(2x+1)= | | 8(x+2)=7x-7 | | 1.35p=40.5 | | -4+x=6+x |

Equations solver categories